Reconstructing Aurat and Hifz an-Nafs for the Protection of Women in Digital Spaces Based on Islamic Ethics - Farida Syarifah; Lilik Andaryuni (al-Afkar, Journal For Islamic Studies, 2026)
The rapid growth of digital technology has created new spaces for interaction while simultaneously increasing the risk of online gender-based violence against women. In response, the Islamic concepts of aurat and hifz an-nafs within Maqashid Syariah offer a normative-religious approach to digital protection. This study aims to explore how these two principles can serve as a foundational framework for developing a secure and just digital environment for women. Employing a qualitative, descriptive-analytical method based on literature review, data were sourced from tafsir, fiqh, policy documents, and contemporary research. Findings reveal that aurat signifies not only physical modesty but also the safeguarding of dignity, privacy, and identity in digital interactions. Meanwhile, hifz an-nafs promotes protection against digital violence in both physical and psychological forms. The integration of these concepts supports the formation of ethical, gender-sensitive policies and underscores the relevance of Islamic values in shaping a safe digital culture. In conclusion, aurat and hifz an-nafs can provide a comprehensive ethical framework for digital protection. Further studies are encouraged to examine their application in cyber law and digital education.